2008
DOI: 10.1017/s0029665108005983
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in then-3 fatty acid content of tissues

Abstract: Dietary n-3 PUFA have many beneficial effects on cell and tissue function and on human health. In mammals the n-3 essential fatty acid α-linolenic acid (ALNA) can be converted into longer-chain (LC) n-3 PUFA such as EPA and DHA via a series of desaturase and elongase enzymes that are mainly active in the liver. Human studies have identified that males and females appear to differ in their ability to synthesise EPA and DHA from ALNA, with associated differences in circulating concentrations. Based on studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
147
3
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 55 publications
15
147
3
2
Order By: Relevance
“…Nonetheless, as observed by others (Childs et al, 2008;Childs et al, 2010a;Extier et al, 2010), changes in tissue fatty acid levels due to both dietary and gender influences occurred even in the brain (Du et al, 2011). Likewise, we found that the dairy fatbased diets attenuated the gender influence to a greater extent than the palm-oil-based diets.…”
Section: Discussionsupporting
confidence: 87%
“…Nonetheless, as observed by others (Childs et al, 2008;Childs et al, 2010a;Extier et al, 2010), changes in tissue fatty acid levels due to both dietary and gender influences occurred even in the brain (Du et al, 2011). Likewise, we found that the dairy fatbased diets attenuated the gender influence to a greater extent than the palm-oil-based diets.…”
Section: Discussionsupporting
confidence: 87%
“…Synthesis of 22 : 5n-3 and 22 :6n-3 appeared to be independent of 20 :5n-3 status and to be down-regulated in adults compared to juveniles. The sex difference in the proportion of 22 :6n-3, but not 22 : 5n-3, in adults is consistent with greater conversion of 22 :5n-6 to 22 : 6n-3 in women than men (1)(2)(3)(4) and with the suggestion that these metabolic reactions are regulated independently of the conversion of 18 :3n-3 to 20 :5n-3 (8) . Our findings support the suggestion that puberty represents an important influence on PUFA metabolism which acts through several regulatory loci.…”
supporting
confidence: 69%
“…We found that total -3 levels were signifi cantly elevated in our IBS cohort compared with controls without any alteration in total -6 levels. The factors behind this shift toward the -3 fatty acids are diffi cult to exdid not take account of possible gender differences in PUFA profi les that have been previously reported ( 35 ).…”
Section: Discussionmentioning
confidence: 93%